2022
DOI: 10.21203/rs.3.rs-1430342/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responses and tolerance mechanisms of K. paniculate seedlings under lead stress: physiological indicators, morphological distribution, enrichment effects and microstructure

Abstract: Phytoremediation could be an alternative strategy for lead (Pb) contamination, The physiological mechanisms of plant resistance to Pd contamination are of less concern. In this study, Different concentrations of Pb solutions were added to explore the growth of Koelreuteria paniculate (Sapindaceae). physiology and microstructure of K. paniculate were determined. The results showed that plant growth increased up to 123.8% and 112.7% relative to the control group when the lead concentration was 200 and 400 mg/L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…However, there have been reports of decreased biomass allocation, which can be attributed to heavy metal concentrations in the soil and the growth strategies adopted by different plant species. This can lead to lower absorption or avoidance of pollutant uptake by roots [60][61][62]. In fact, Yang, et al [63] found that invasive species, such as Biden frondosa, Erigeron Canadensis, Alternanthera philoxeroides and Cynodon dactylon, accumulated significantly lower levels of Pb in both roots and shoots compared to native species.…”
Section: Morphological Plasticitymentioning
confidence: 99%
“…However, there have been reports of decreased biomass allocation, which can be attributed to heavy metal concentrations in the soil and the growth strategies adopted by different plant species. This can lead to lower absorption or avoidance of pollutant uptake by roots [60][61][62]. In fact, Yang, et al [63] found that invasive species, such as Biden frondosa, Erigeron Canadensis, Alternanthera philoxeroides and Cynodon dactylon, accumulated significantly lower levels of Pb in both roots and shoots compared to native species.…”
Section: Morphological Plasticitymentioning
confidence: 99%